Stability Constants of Mixed-Ligand Complexes of Cu(II) with Oxprenolol HCl as Pharmaceutical Ligand and Some Biologically Active Ligands - Alturiqi, Amani S. (Asian Journal of Chemistry, 2017)
The oxprenolol-Cu(II) complexes have been used as DNA constituents (L) and antihypertensive drug. In this study, the formation constants of these complexes, which formed in H2O/MeOH (80:20) solution and their concentration distributions were assessed at ionic strength of 0.1 mol/L NaClO4 at 25 °C. Stability constants and the values of D log K for the targeted complexes have also been evaluated depending on pH meter.